Overview of Ocean Carrier Liability Exceptions Under the Rotterdam Rules and the Hague-Hague/Visby Rules - Katsivela, Marel (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2010)
The present article constitutes an overview of the ocean carrier liability exceptions contained in the newly adopted Rotterdam Rules and those present in the Hague-Hague/Visby Rules. Such an overview aims at identifying the main changes brought about by the Rotterdam Rules to the existing Hague-Hague/Visby exculpatory causes. Canadian, English and United States case law and doctrine commenting on the Hague-Hague/Visby Rules liability exceptions are used as the basis for the present comparative study.